Layanan pada PT. Citra Jelajah Informatika Bandung: Key to Improving Customer Satisfaction - Nenden Sondari Robianty; Budi Prasetiyo (Penerbit Goodwood, 2024)
Purpose: This study is motivated by the increase in internet users in Indonesia. The research examines the impact of services on customer satisfaction at PT. Citra Jelajah Informatika. Methodology/approach: The research method used in this study is a qualitative method. In this research, the unit of analysis used is the individual unit, encompassing all complaints from clients of PT. Citra Jelajah Informatika. Results/findings: The company is facing evaluation issues for progress, especially concerning service quality and slow complaint handling. The high number of customer complaints is attributed to the limited Human Resources. Limitations: This research is planned to involve all employees of PT. Citra Jelajah Informatika and its clients. Contribution: The author found several alternative solutions to problems related to customer complaints, including improving service quality and customer service responsiveness. The proposed solution involves training for the customer service team, regular communication between customer service and NOC, implementation of complaint SOPs, additional human resources in customer service and NOC support, notification of complaints during disruptions, ensuring network stability, early notification from customer service about service disruptions , and special activities (Customer Relations) to obtain regular customer.